Enhancing Halal procurement practice among hotel in Malaysia / Sara Shakira Shari … [et al.] - Shari, Sara Shakira; Mohd Moid, Muzairihana; Supian, Kamisah; Suhaimi, Anora Shaliaty (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The demand for Halal products has increased significantly from both Muslims and non-Muslim communities throughout the world. This phenomenon is attributed to the fact that Halal food has better cleanliness and safety amid growing concerns for health. Few studies have shown that the supply chain plays a crucial role in ensuring that the products are Halal compliant and that procurement is one of the main branches. In the hotel industry, the procurement department is responsible for ensuring that raw materials are arranged, purchased, delivered, and consumed effectively. Transparency, supplier engagement, and risk management are three elements that are highlighted matters in the hotel industry. Previous studies have shown that these three elements have a significant role in enhancing procurement practice in organisations. This paper focuses on the elements and effectiveness of Halal procurement practises among Malaysian hotels. This study also aims to help companies evaluate their Halal procurement practises and develop effective strategies to ensure that food products follow Halal guidelines that ultimately enhances business performance.